Role of FLT3 Receptor in Peripheral White Blood Cells of Newly Diagnosed Diffuse Large B Cell Lymphoma Patients and Healthy Individuals: A Preliminary Study - Nandasena, C.K.; Jayathilake, P.W.D.C.C.; Suresh, S.; De Silva, A.D.; Perera, I.C.; Kottahachchi, D.U. (University of Colombo, 2024)
Diffuse Large B Cell Lymphoma (DLBCL) is a major subtype of lymphoma. FLT3 (FMS-related-receptor-tyrosine-kinase-3) receptor stimulates the proliferation of ...
Keywords: DLBCL; Absolute WBC Counts; NLR; LMR; FLT3